Upaya Kepala Sekolah Menanggulangi Kenakalan Anak Gunung - Titin Mariatul Qiptiyah; Ahmad Rosidi; Muhamad Mukit (Al-Riwayah : Jurnal Kependidikan, 2021)
The quality of an educational institution depends on the principal as an educational leader. The principal has a very important role in advancing the institution he leads, so the madrasa principal serves as a supervisor, supervisor in everything that happens at school. All problems that occur in the madrasa must get the right solution from the head of the madrasa. The problem of student delinquency is no exception, in this case the head of the madrasa must make every effort to suppress student delinquency cases in order to create a conducive learning environment so that educational goals can be achieved. This study aims to: 1) describe the forms of delinquency committed by students of MTs Al Imam Cumedak, 2) describe the factors that cause student delinquency, 3). Describes the efforts and impacts of the madrasa principal in tackling student delinquency at MTs Al Imam Cumedak. And this type of research is descriptive qualitative. From the results of the research that has been carried out, it can be concluded that in general the forms of student delinquency at MTs Al Imam Cumedak, Sumberjambe sub-district, Jember Regency are classified as mild delinquency not breaking the law such as truancy, crowded in class, not wearing uniforms and others. The causes of student delinquency at MTs Al Imam are family and school factors. Meanwhile, what is done by the principal in tackling student delinquency is to increase exemplary behavior and instill the noble values ​​of the teachings of ahlusunnah waljamaah so that students can get used to having akhlaqul karimah wherever they are.